Estudo histórico do princípio da luz: Criação de uma cartilha para divulgação científica sobre a natureza dos fenômenos luminosos que opuseram Fermat & Descartes - Genuino, Luiz Carlos Carneiro (2018)
The discussions about Fermat (1601-1665) and Descartes (1596-1650) in certain didactic texts are sometimes incomplete, prioritizing more the mathematical aspect in the form of exercises at the end of the chapter of Geometric Optics, leading to a distorted view or erroneous of the theoretical and historical aspects existing in the discussions of the reflection and refraction of light. In this perspective, as a general objective, the present work analyzes the historical account of the nature of the luminous phenomena that opposed Fermat to Descartes, through his letters to Descartes, Marin Cureau De La Chambre and other Cartesians, from 1648, trying to understand if its principle in its initial formulation was based on the scientific context of the time. For this, we prioritize the reading of the original letters, the books "La lumiére" by De La Chambre and the "La Dioptrique" by Descartes, as well as other reliable and reliable sources such as: Ramos (2010), Moreira (1998), Paty 1998) and others, to avoid the perpetuation of conceptual and historical errors. As a pedagogical tool, we use the History and Philosophy of Sciences associated to the use of experimental activities for the improvement of teaching in the various school levels. And for the educational product, with the data obtained in this study, we produced a didactic-pedagogical material (of the Paradidático-Cartilha type) that aims at the safe dissemination of this historical episode that can be used in the classroom by teachers and will also serve to those who have the interest to study on the subject.